Impact of Political Events on Stock Market: Evidence from Pakistan - Mahmood, Shahid; Irfan, Muhammad; Iqbal, Saeed; Kamran, Muhammad; Ijaz, Ali (Journal of Asian Business Strategy, 2014)
In this paper it is examined that how much political events impact the KSE-100 index returns, fifty major political events are selected from the period of 1998 to 2013. To calculate the abnormal returns, event study methodology is applied and KSE-100 index returns data for 30 days before and 60 days after happening of an event are also collected. Results of each window verify that negative abnormal returns are observed some days before and some days after happening of an event. This study helps the investor to judge the effect of political events on KSE-100 index returns and develop strategy according to the political environment. Only major political events are selected for a selected time horizon which is not covering the all political episodes. Political conditions vary country to country and period to period. Further researches can be made by selecting different political events for any other country. This study contributes in literature and verifies the significant relationship between political events and stock market returns.